Measure for measure: a response to Steven Mailloux - J. Frow (Law Text Culture, 1997)
Steven Mailloux tells two stories from Foucault about the birth of Truth in the 'historical division' between an older, performative mode of truth-telling and a mode of truth based in the claim to separateness from untruth. The first story is taken from Foucault's inaugural lecture at the College de France, 'The Order of Discourse' , the second from a summary of a lecture series published in English as 'History of Systems of Thought'. My response is focused on a conflict over the interpretation of these stories.